DENOMINASI MAYORITAS MUSLIM TERHADAP MINORITAS MUSLIM DI INDONESIA: STUDI FATWA MUI TENTANG ALIRAN KEBERAGAMAAN - Wicaksono, Syafril; Al-Asy Ari, Khoirul Hadi; El Adibah, Elisa Dourotun Nafis; Iffahasanah, Iffahasanah (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2024)
This research is a library research study on the results of fatwas produced by the MUI, the Indonesian Ulama Council, with the dimensions of several fatwas that are